Parents' Perceptions of the Learning System During the Covid-19 Pandemic at SMA Negeri 8 Longgar, Aru Islands Regency - Paulus Robert Tuerah; Sara Djontar; Romi Mesra (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2023)
The purpose of this study was to find out how parents perceived the learning system during the Covid-19 pandemic in SMA Negeri 8 Loose students. This study collected data through interviews, observation and documentation using a qualitative methodology. The findings of this study suggest that parents' perceptions of a good answer are that they can hang out with their children to strengthen their bond and personally monitor their children while they are learning. Parents expressed concern that online learning during the Covid-19 outbreak was impacting the quality of their children's learning. Meanwhile, the children's positive responses indicated that online learning was fun because someone was always there to help them when they had assignments from the teacher. The negative response is that students struggle to understand the teacher's assignment. As a result, parents must provide additional encouragement and attention to their children so that their learning activities continue to run smoothly even if they are not in front of the teacher as usual.